2023
DOI: 10.1038/s41467-023-37120-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous intercalated metal-organic framework active materials for fast-charging non-aqueous Li-ion capacitors

Abstract: Intercalated metal-organic frameworks (iMOFs) based on aromatic dicarboxylate are appealing negative electrode active materials for Li-based electrochemical energy storage devices. They store Li ions at approximately 0.8 V vs. Li/Li+ and, thus, avoid Li metal plating during cell operation. However, their fast-charging capability is limited. Here, to circumvent this issue, we propose iMOFs with multi-aromatic units selected using machine learning and synthesized via solution spray drying. A naphthalene-based mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Ogihara et al reported an intercalated MOF-based active electrode material for Li-ion-based ESDs. 253 They used 0.8 V potential for intercalation of Li-ions in the MOF matrix. This hybrid ESD shows an 85% retention capacity at 400 mA g −1 .…”
Section: Ternary Nc Ie Carbon Material/cp/mo-base...mentioning
confidence: 99%
“…Ogihara et al reported an intercalated MOF-based active electrode material for Li-ion-based ESDs. 253 They used 0.8 V potential for intercalation of Li-ions in the MOF matrix. This hybrid ESD shows an 85% retention capacity at 400 mA g −1 .…”
Section: Ternary Nc Ie Carbon Material/cp/mo-base...mentioning
confidence: 99%
“…These materials offer several advantages such as being non-toxic, abundant on the planet, and cheap and provide good results when gravimetric methods are used (Banerjee & Parise 2011). Li-dicarboxylates may be good candidates as electrode materials for eco-friendly alternatives to other inorganic materials, and have been reported for use in battery applications (Armand et al, 2009;Ogihara et al, 2014Ogihara et al, , 2023Mikita et al, 2020). To improve our chemistry and electrode applications, we investigated CNs using disulfonate ligands.…”
Section: Chemical Contextmentioning
confidence: 99%
“…When used as lithium-ion anodes, well-ordered 3D channels can lead to improved rate performances and capacity. 35–39 Although obtaining stable MOF or COF anodes for fast-charging LIBs is still challenging, the construction of ordered 3D ordered lithium-ion diffusion channels is instructive for high-rate organic anode materials.…”
Section: Introductionmentioning
confidence: 99%